Outcome of Instrumentation in Caries Spine (Journal of Pakistan Orthopaedic Association, 2013)
Objectives: We aimed to determine the efficacy of instrumentation in caries spine and to present the long term clinical results of the patients treated with the help of this protocol.Study design: Retrospective cross sectional study Study setting: Department of Orthopedic Surgery Unit II, Mayo Hospital Lahore, Pakistan Duration: From 2008 to 2010 Material and Methods: 37 patients (22 females, 15 males) with a mean age of 32 years were operated for the management of caries spine. Debridement of the affected site of the spine was done followed by instrumentation and fusion in all the patients. The indications for surgery were no response to medical treatment for three months, persistent pain and instability, progressive neurological deficit and angular deformity of the spine. Anti-tuberculous therapy was continued postoperatively for one year. All the patients were telephonically approached through the contact numbers given at the time of their admission and patients were called to the hospital for evaluation. 31 patients responded to our call and therefore 31 patients were included in the study. Oswestry Disability Index (ODI) was calculated for individual patient after 24 months of surgery. Results: Out of the total 31, 2 patients (6.6%) had no disability according to the Oswestry Disability Index. 23 patients (73.3%) had mild disability whereas 4 patients (13.3%) had moderate disability. Only 1 patient (3.3%) had severe disability and 1 patient was completely disabled Conclusion: Spinal instrumentation in tuberculous spondylitis has good long term functional outcome.Key words: Caries spine, Instrumentation, Disability